Comparison of clinical and economic burden of pulmonary arterial hypertension patients with and without connective tissue disease treated with macitentan. (3rd October 2022) - Worden, C; Shoaib-Agwan, S; Singh, R; Zhang, W; Panjabi, S
Abstract: Introduction: Patients with pulmonary arterial hypertension (PAH) and connective tissue disease (CTD) have a poorer prognosis than those diagnosed with other PAH etiologies. Purpose: To compare the clinical and economic burden among PAH patients with and without CTD (PAH-CTD/PAH non-CTD) treated with macitentan. Methods: This retrospective study used the Optum Clinformatics DataMart to identify PAH-CTD and PAH non-CTD patients aged ≥18 years and prescribed macitentan from 01JAN2015–30JUN2019. The index date was the date of the first macitentan claim. Patients had to have ≥12 months of continuous enrollment before index and were followed until earliest of macitentan discontinuation, health plan disenrollment, death, or study end. Patients in the PAH-CTD cohort had to have a claim for a CTD condition at any time during the 12-month baseline period. Patients with a baseline claim for any PAH medication, chronic thromboembolic pulmonary hypertension, prior atrial septostomy or lung transplant were excluded. Descriptive analysis comprised means, standard deviations, medians, and interquartile ranges for continuous variables and frequencies and percentages for categorical variables. Multivariable analyses (Cox proportional hazards and generalized linear models) adjusting for baseline characteristics were used to compare time to PAH-related and all-cause hospitalization, disease progression (death, lung transplant, atrial septostomy or addition of intravenous/subcutaneous prostanoids), and PAH- and all-cause related medical (inpatient and outpatient) costs between the two cohorts with PAH non-CTD as reference. Results: The analysis included 203 PAH-CTD and 750 PAH non-CTD patients treated with macitentan. Versus PAH non-CTD, PAH-CTD patients were younger, had proportionately more females, and lower Charlson Comorbidity Index (CCI) scores (Table). The proportion of patients with a baseline hospitalization, length of stay and inpatient costs were similar across groups. There were no significant differences observed in time to PAH-related hospitalization (hazard ratio [HR]=0.99; p=0.910), all-cause hospitalization (HR=1.13; p=0.195), or disease progression (HR=1.00; p-value=0.973) for the PAH-CTD cohort (PAH non-CTD as reference). All-cause medical costs were similar between the cohorts (3, 836 per patient per month [PPPM] for PAH CTD vs 3, 521 PPPM for PAH non-CTD, p=0.362). PAH-CTD patients incurred higher mean PAH-related medical costs vs PAH non-CTD (2, 806 PPPM vs 1, 961 PPPM, p=0.047). Conclusion: The study suggests that risk of all-cause and PAH-related hospitalization and disease progression did not differ for PAH-CTD and PAH non-CTD patients. Treatment with macitentan in the real world appears to confer similar clinical benefits in both PAH-CTD and PAH non-CTD groups. All-cause costs did not differ between the two cohorts but PAH-related costs were significantly higher in PAH-CTD patients suggesting an incremental burden associated with CTD. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Janssen Scientific Affairs, LLC